2018
DOI: 10.1002/cphc.201800778
|View full text |Cite
|
Sign up to set email alerts
|

TiNF and Related Analogues of TiO2: A Combined Experimental and Theoretical Study

Abstract: Aliovalent anion substitution in inorganic materials brings about marked changes in properties, as exemplified by N,F‐codoped metal oxides. Recently, complete substitution of oxygen in ZnO by N and F was carried out to generate Zn2NF. In view of the important properties of TiO2, we have attempted to prepare TiNF by employing an entirely new procedure involving the reaction of TiN with TiF4. While the reaction at low temperature (450 °C) yields TiNF in the anatase phase, reaction at a higher temperature (600 °C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The band widths of p orbitals of N and F at the top of valence band are 1.33 eV and 1.31 eV respectively. Earlier studies showed the VBM of TiNF and Cd 2 NF consists primarily of N‐2 p states and F‐2 p states lie around –2 eV with respect to VBM , . The p orbitals of N at the top of valence band has a band width of 0.68 eV in TiNF which is small compared to that in Hg 2 NF.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The band widths of p orbitals of N and F at the top of valence band are 1.33 eV and 1.31 eV respectively. Earlier studies showed the VBM of TiNF and Cd 2 NF consists primarily of N‐2 p states and F‐2 p states lie around –2 eV with respect to VBM , . The p orbitals of N at the top of valence band has a band width of 0.68 eV in TiNF which is small compared to that in Hg 2 NF.…”
Section: Resultsmentioning
confidence: 94%
“…Materials such as Ca 2 NF, Sr 2 NF and Ba 2 NF have been reported, but the consequences of chemical ordering of N 3– and F – on the anion sublattice, structure and electronic properties have not been addressed . We have examined the change in the band gap with the substitution of N 3– and F – in ZnO and TiO 2 wherein the materials become colored and allow visible light excitation , . Substitution of sulfide anion in place of the oxide anion does not have such significant effects .…”
Section: Introductionmentioning
confidence: 99%
“…Aliovalent anion substitution in oxides and sulfides such as TiO 2 , ZnO, CdO, and CdS has already been shown to modify the band structure and electronic properties of these materials, making them suitable for catalysis applications . Anionic substitution by a simple solid-state synthesis, O by N and F in TiO 2 (e.g., TiNF), , ZnO (e.g., Zn 2 NF), and CdO (e.g., Cd 2 NF) and sulfur­(S) by phosphorus (P) and chlorine (Cl) in CdS (e.g., Cd 2 PCl) gives rise to novel properties. Substitution changes the electronic structure and optical properties of the materials; therefore, this strategy would be interesting for the GaN to substitute C in place of N in the presence of O impurity.…”
Section: Introductionmentioning
confidence: 99%